Effectiveness extract of Crataeva nurvala leaves as insecticide against Spodoptera litura - Ma'rufah, Hastini; Nugroho, L. Hartanto; Sukirno, Sukirno (Communications in Science and Technology, 2024)
Spodoptera litura Fabricius, an insect pest, is known to be highly detrimental to farmers for having a variety of host plants. The application of synthetic insecticides to eradicate pests has been proven to bring many negative impacts, especially regarding the cases of resistance and the presence of residues that are harmful to the environment. This study aims to study the effectiveness of potential bioactive compounds of Tigarun leaves (Crataeva nurvala Buch. Ham) as the biochemical insecticides of S. litura. Tigarun plant, widely used as traditional medicine, contains the potential bioactive compounds for bioinsecticides. The extraction process was carried out by maceration using methanol and ethyl acetate solvents, which were then identified for compound content through GCMS analysis. The bioassay method was performed using the test parameters of mortality and eating power of S. litura instar II larvae. The crude extracts from the two solvents obtained showed their effectiveness as bioinsecticides against S. litura instar II larvae. The highest efficacy occurred in the ethyl acetate extract using the contact poison method with the lowest LC50 value of 0.11. Both extracts were also able to reduce the appetite and provide sublethal effects on S. litura larvae. GCMS analysis indicated the presence of several compounds as insecticides in both Tigarun leaf extracts such as 1,2,3-Propanetriol (CAS) Glycerol; Tetradecanoic acid (CAS) Myristic acid; 9-Hexadecenoic acid; n-Hexadecanoic acid; oleic acid; Heneicosane; and Neophytadiene and several other compounds. This study recommends Tigarun leaf extract (C. nurvala) ethyl acetate with the contact method as a natural insecticide against S. litura.